Multi Actors’ Perspectives on Environment, Social, and Governance Reporting in Listed Companies in Sri Lanka - Nanayakkara, M.S.; Shamil, M.M.; Karunarathne, W.V.A.D. (University of Jaffna, 2023)
This study explores multi-actors' perspectives on Environment, Social, and Governance (ESG) reporting in Sri Lankan listed companies. While most studies have explored the perceptions of managerial and non-managerial stakeholders regarding ESG reporting in developed countries, there is a scarcity of research in developing countries. Only a few studies have yet addressed the phenomenon of ESG reporting in Sri Lanka by analysing the multi-actors’ perspectives. On the other hand, most previous studies have primarily investigated internal organizational factors that influence ESG reporting using a quantitative method. In this study, ESG reporting was assessed through the perspectives of multi-actors. Qualitative methodology is used to analyze the participants’ perspectives following an interpretivist approach. Using semi-structured in-depth interviews, exploratory data was collected related to the research topic. Participants for the sample were selected based on engagement with ESG activities, knowledge, and personal experience. Interviewees participated in face-to-face and online interviews via Zoom. Thematic analysis was performed to identify the common themes from the respondents' explanations. Awareness, reporting guidelines, stakeholders’ demands, top management commitment, capturing information, and education are the major themes identified in ESG reporting in listed entities. The study contributes to understanding the phenomenon of ESG reporting and it presents findings that may be useful for theory and practice. Finally, the study provides empirical evidence for regulatory authorities and policymakers on the actions and methods for developing ESG reporting in listed companies in Sri Lanka.
Keywords: ESG Reporting; Multi-Actors; Perspectives; Thematic Analysis; JEL Classification: G31